2011
DOI: 10.3109/02770903.2011.623334
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Cyclophilin Levels Associate with Parameters of Asthma in Phenotypic Clusters

Abstract: Objective Leukocyte persistence during chronic (quiescent) phases of asthma is a major hallmark of the disease. The mechanisms regulating these persistent leukocyte populations are not clearly understood. An alternative family of chemoattracting proteins, cyclophilins, has recently been shown to contribute to leukocyte recruitment in animal models of allergic asthma. The goal of this study was to determine if cyclophilins are present in asthma patients during the chronic phase of disease, and to investigate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…These primary cell cultures were obtained from healthy donors and included astrocytes, fibroblasts, bronchial epithelial cells, nasal epithelial cells, RPE cells and Schwann cells. These cells were chosen because they were currently studied in our laboratory in the context of different diseases such as brain tumors (astrocytes and GBM cell lines) [11], asthma (bronchial and nasal epithelial cells) [21], age related macular degeneration (RPE cells) [7], and neurofibromatosis type-1 (Schwann cells) [22]. Fibroblasts cells were included as a reference to the primary cell cultures because often primary cell cultures contain fibroblasts cells that might confound the true secretome.…”
Section: Discussionmentioning
confidence: 99%
“…These primary cell cultures were obtained from healthy donors and included astrocytes, fibroblasts, bronchial epithelial cells, nasal epithelial cells, RPE cells and Schwann cells. These cells were chosen because they were currently studied in our laboratory in the context of different diseases such as brain tumors (astrocytes and GBM cell lines) [11], asthma (bronchial and nasal epithelial cells) [21], age related macular degeneration (RPE cells) [7], and neurofibromatosis type-1 (Schwann cells) [22]. Fibroblasts cells were included as a reference to the primary cell cultures because often primary cell cultures contain fibroblasts cells that might confound the true secretome.…”
Section: Discussionmentioning
confidence: 99%
“…CyPA has been found to be secreted into the extracellular space by several types of cells, such as foam cells (14), vascular smooth muscle cells (15), and macrophages (16). In patients, higher levels of soluble extracellular CyPA can be detected under inflammatory conditions, for example, in nasal fluids of patients with asthma (35), in plasma of patients with type 2 diabetes (16), and in serum of patients with coronary artery disease (36). The exact mechanism by which CyPA is secreted from the intracellular to extracellular space has not been well described.…”
Section: Discussionmentioning
confidence: 98%
“…Basigin acts as a matrix metalloproteinase inducer and promotes renal fibrosis, as recently demonstrated in mice [35]. Interestingly, recent clinical and in vivo contributions indicated that increase in extracellular PPIB levels is not only restricted to renal cells and could also result from pro-inflammatory or immuno-allergic phenomenons, suggesting that extracellular mobilization of PPIB is not specific of CsA [30,43,44]. Indeed, overexpression of PPIB in nasal wash samples of asthma patients was previously reported by Stemmy et al who suggested the detection of PPIB as a potential biomarker for clinical parameters of asthma severity [43].…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, recent clinical and in vivo contributions indicated that increase in extracellular PPIB levels is not only restricted to renal cells and could also result from pro-inflammatory or immuno-allergic phenomenons, suggesting that extracellular mobilization of PPIB is not specific of CsA [30,43,44]. Indeed, overexpression of PPIB in nasal wash samples of asthma patients was previously reported by Stemmy et al who suggested the detection of PPIB as a potential biomarker for clinical parameters of asthma severity [43]. These authors also indicated that blocking the function of cyclophilins during the chronic phase of asthma may provide a potential therapeutic strategy for regulating disease chronicity and severity in a murine model of chronic allergic asthma [44].…”
Section: Discussionmentioning
confidence: 97%